Hyaluronic acid-modified liposomal honokiol nanocarrier: Enhance anti-metastasis and antitumor efficacy against breast cancer. (1st May 2020) - Wang, Jing; Liu, Dan; Guan, Shuang; Zhu, Wenquan; Fan, Li; Zhang, Qi; Cai, Defu
Highlights: Hyaluronic acid functionalization endows the liposomes to actively target tumor cells. Honokiol shows great promise in breast cancer therapy, both in vitro and in vivo . The nano-liposomes enhance anti-metastasis and antitumor efficacies against breast cancer. Abstract: In an effort to enhance antitumor and anti-metastasis of breast cancer, honokiol (HNK) was encapsulated into hyaluronic acid (HA) modified cationic liposomes (Lip). The prepared HA-Lip-HNK had a spherical shape with a narrow size distribution. The enhanced antitumor efficacy of HA-Lip-HNK was investigated in 4T1 cells in vitro, wherein flow cytometry and confocal microscopy analysis revealed its HA/CD44-mediated greater cellular internalization. As anticipate, the significant cytotoxicity of the HA-Lip-HNK was also observed in 4T1 tumor spheroids. Furthermore, the superior prevention of tumor metastasis by HA-Lip-HNK was verified by in vitro anti-invasion, wound healing and anti-migration assessments, and in vivo bioluminescence imaging in pulmonary metastasis model. Finally, compared with unmodified liposomes, the HA-Lip-HNK exhibited higher tumor accumulation, and achieved a tumor growth inhibition rate of 59.5 %. As a result, the HA-Lip-HNK may serve as a promising tumor-targeted drug delivery strategy for the efficient therapy of metastatic breast cancer.